Pembinaan Karakter Pemuda Kristiani dalam Perspektif Nilai Longko’ di Era Disrupsi - Febriani Febriani; Desi Ratna Sari; Anita Nengsi Tandi Bua' (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2020)
Longko’ values are part of the values that are lived by the Toraja people. This value needs to be investigated more deeply concerning fostering the character of Christian youth. However, the challenges of Christian youth also live in a reproducible era, which is the era of changing order very quickly due to the influence of technology, especially the industrial revolution 4.0. The church needs to consider the steps to accommodate cultural values, namely the value of longko’, and the challenges of the era of disruption. This study uses a qualitative approach to the types of social and theological research studies to be able to produce an appropriate character building model. This research concludes that the formation of Christian youth character in the perspective of longko’ values in the era of corruption resulted in three main study focuses, namely on the aspect of fostering Christian values for Christian youth by the Church in the perspective of longko’ values in the era of disruption. Second, fostering the lifestyle of Christian youth by the church in the perspective of longko’ values in the era of disruption. The third is the fostering of the habit of living full of the Holy Spirit for Christian youth as a result of the perspective of longko’ values in the era of disruption. AbstrakNilai longko’ merupakan bagian yang menjadi nilai-nilai yang dihidupi oleh orang Toraja. Nilai ini perlu diselidiki lebih dalam dalam kaitannya dengan pembinaan karakter pemuda kristiani. Namun demikian tantangan pemuda kristiani juga hidup di era yang diruptif yaitu era perubahan tatanan yang sangat cepat karena pengaruh teknologi terkhusus revolusi industri 4.0. Gereja perlu mempertimbangakan langkah akomodasi nilai budayawi yaitu nilai longko’ dan tantangan era disrupsi. Tujuan penelitian ini merumuskan pembinaan karakter pemuda Kristiani dalam perspektif budaya longko’ di era disrupsi. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi penelitian sosial dan teologis untuk dapat menghasilkan suatu model pembinaan karakter yang tepat. Penelitian ini menghasilkan kesimpulan bahwa pembinaan karakter pemuda kristiani terhadap dalam perspektif nilai longko’ di era disrupsi menghasilkan tiga fokus kajian utama yaitu pada aspek pembinaan nilai-nilai Kristiani bagi pemuda Kristiani oleh gereja dalam perspektif nilai longko’ di era disrupsi. Kedua, pembinaan gaya hidup pemuda Kristiani oleh gereja dalam perspektif nilai longko’ di era disrupsi. Ketiga pembinaan kebiasaan hidup penuh Roh Kudus bagi pemuda Kristiani akibat dalam perspektif nilai longko’ di era disrupsi.